Determinants of Loan Loss Provisioning for Commercial Banks in the United Kingdom - Li, Yuzhu (2014)
This timely empirical study investigates the determinants of loan loss provisioning for commercial banks in the United Kingdom. A sample of 23 commercial banks in the UK are used in a dynamic panel dataset covering a period of 8 years from 2006 to 2013. This period is of great value for research since it covers a period of transition from Basel I to II and global financial crisis from 2008 to 2009. Loan loss provisions are found to be procyclical with a negative relationship with GDP growth rate during this period. Income smoothing and capital management were also found to be significant in this study. Z-score, which measures insolvency risk, is found to be negatively related to LLPs. It indicated that a high of loan loss provisions is associated with insolvency to a certain degree. However, there is no evidence showing that technical efficiency affects loan loss provisions of commercial banks in the UK.